2021
DOI: 10.1080/10428194.2021.1933478
|View full text |Cite
|
Sign up to set email alerts
|

microRNAs as the biomarkers of chemotherapy-induced peripheral neuropathy in patients with multiple myeloma

Abstract: Multiple myeloma (MM) is a malignant, incurable neoplastic disease. The currently used treatment significantly improves the prognosis and extends the survival time of patients. Unfortunately, a common side effect of the therapy is peripheral neuropathy, which may lead to dose reduction or complete treatment discontinuation/modification. In this study, we examined the changes in plasma levels of circulating miRNAs in myeloma patients to define potential factors characteristic for drug-induced peripheral neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…This result was consistent with previous studies using sequential treatment [7,8]. Subcutaneous injection (SC) and the once-weekly schedule of bortezomib in our study may be the reason for the significantly lower rates of peripheral neuropathy, which was also reported in several studies [8,[14][15][16], and most importantly, the efficacy of SC is not compromised compared with IV administration [17]. Additionally, Toor et al [18] reported that grade III/ IV peripheral neuropathy (PN) was more associated with the Vd and IMiD combination group (15.7%) than the VCd group, in which no grade III/IV PN was noted.…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with previous studies using sequential treatment [7,8]. Subcutaneous injection (SC) and the once-weekly schedule of bortezomib in our study may be the reason for the significantly lower rates of peripheral neuropathy, which was also reported in several studies [8,[14][15][16], and most importantly, the efficacy of SC is not compromised compared with IV administration [17]. Additionally, Toor et al [18] reported that grade III/ IV peripheral neuropathy (PN) was more associated with the Vd and IMiD combination group (15.7%) than the VCd group, in which no grade III/IV PN was noted.…”
Section: Discussionsupporting
confidence: 93%
“…Blocking miR-155 expression reduced mechanical allodynia and thermal hyperalgesia in rats [ 39 ]. In our previous study [ 40 ], we showed the relationship between changes in plasma miRNA expression (miR-22-3p; miR-23a-3p; miR-24-3p) in patients with MM with the development of drug-induced peripheral neuropathy. These studies confirmed that the treatment affects epigenetic modification and may be related to the development of neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…9 Pregabalin and gabapentin are also used to prevent peripheral neuropathy in MM patients. 10 However, there are no evidence-based therapies to prevent chemotherapy-induced peripheral neuropathy. Varicella zoster virus vaccine has been documented to reduce the incidence of HZ and PHN in MM patients.…”
Section: Discussionmentioning
confidence: 99%